2016
DOI: 10.1111/famp.12217
|View full text |Cite
|
Sign up to set email alerts
|

The Meta Marriage: Links Between Older Couples' Relationship Narratives and Marital Satisfaction

Abstract: Drawing upon a relatively understudied population and a unique observational task, the current study sought to examine how older couples' interactional behaviors during a relationship narrative task were associated with marital satisfaction over time. Using observational data from a sample of 64 older, higher-functioning married couples, we analyzed a series of Actor-Partner Independence Models (APIM) to explore how couples' interactional behaviors during a relationship narrative task were associated with spou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 51 publications
0
10
0
2
Order By: Relevance
“…As a result, parents may perceive higher burden when caring for PLS due to the sense of guilt, blame, and anger that results from their situation [18,57,58]. In contrast, spouse caregivers may normalize caregiving as part of their marital role as reflected in marriage vows, such as "in sickness and in health" or "until death do us part" [59][60][61]. Spouses may thus experience less conflict between their caregiver roles and other family and work-related roles they have, and thus experience less subjective burden [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, parents may perceive higher burden when caring for PLS due to the sense of guilt, blame, and anger that results from their situation [18,57,58]. In contrast, spouse caregivers may normalize caregiving as part of their marital role as reflected in marriage vows, such as "in sickness and in health" or "until death do us part" [59][60][61]. Spouses may thus experience less conflict between their caregiver roles and other family and work-related roles they have, and thus experience less subjective burden [62,63].…”
Section: Discussionmentioning
confidence: 99%
“…Sorokowski et al examined marital satisfaction factors in 33 Western and Eastern countries and concluded that gender, age, the duration of marriage, religiosity/religion, the number of children, economic/social status and class, education, and individualism/collectivism were the main predictors of marital satisfaction (Sorokowski et al, 2017). For example, men are more satisfied with their marriage than women, in Western and non-Western cultures (McCoy et al, 2017). However, cultural differences and variables must be taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, parents may perceive higher burden when caring for PLWS due to the sense of guilt, blame, and anger that results from their situation (27,52,53). In contrast, spouse caregivers may normalize caregiving as part of their marital role as reflected in their marriage vows, such as "in sickness and in health" or "until death do us part" (54)(55)(56). Thus, spouses may experience less conflict between their caregiver roles and other family and work-related roles they have, and thus experience less subjective burden (57,58).…”
Section: Discussionmentioning
confidence: 99%